Traditional herbal interventions for premenstrual syndrome management: a comprehensive literature review - Roni, Md Abul Hasan; Siddique Jami, Abu Bakar; Sultana, Rezwana; Areefin, Prethula; Hossen, Sahadat; Rozina, .; Mohd Yusri, Mohd Yunus (International Scientific Organization, 2024)
Premenstrual syndrome (PMS) causes severe physical and emotional health problems in many women. Due to concerns regarding the potentially harmful effects of conventional treatments, there has been an increased interest in exploring alternative medicines, mainly traditional herbal remedies. This comprehensive literature review employed a rigorous methodology involving extensive data collection from databases such as Scopus®, Web of Science®, and PubMed®, as well as respected publishers like Oxford University Press, Elsevier, Springer Nature, and others. The study examines the properties and potential benefits of Cyperus rotundus, Curcuma longa (turmeric), Aloe vera, Angelica sinensis (Dong Quai), Zingiber officinale (ginger), Crocus sativus (saffron), and Withania somnifera (Ashwagandha) in the context of PMS management. It is important to note that these traditional herbs offer diverse therapeutic properties, which can effectively address both the physical and emotional symptoms of PMS. These herbal interventions have notable analgesic and anti-inflammatory effects, as well as mood-enhancing and adaptogenic qualities. As promising and versatile alternatives to conventional medications, it is essential to conduct further research to prove their efficacy, safety, and ideal use fully. This calls for extensive clinical trials, mechanistic analyses to reveal their mechanisms of action, the creation of standardized formulations, and the adoption of a patient-centered strategy that considers unique preferences and needs. It is possible to significantly improve the holistic approach to PMS management by realizing the full potential of these conventional herbal treatments. This study highlights the vital importance of these herbal interventions in PMS management, ultimately providing women with safer options for PMS relief and an enhanced quality of life.